Payroll Accounting System For Motorcycle Dealers Honda Ramayana In Surabaya - Hariyanti Hariyanti (Pusat Riset dan Inovasi Nasional, 2022)
The success of a company is not only measured by the company's ability to raise funds. The development performance of a company is influenced by several factors, including: natural resources, capital resources, technological resources, facilities and infrastructure resources and human resources. Among the resources above, human resources have a dual function, namely as object resources that are managed, on the other hand as subjects who manage and control all other resources to realize the goals that have been set in each economic activity. Human resources who work in the company receive income in the form of salaries. Salary is one of the important things for every employee who works in a company, because with the salary earned, a person can fulfill their daily needs. Apart from that, salary is an important element that can influence employee performance, because salary is a tool to meet various employee needs, so that with the salary given employees will be motivated to work harder.